Assets and Liabilities Management in Islamic Banking - Bidabad, Bijan; Allahyarifard, Mahmoud (International Journal of Islamic Banking and Finance Research, 2019)
Purpose: In this paper, we are going to consider assets and liabilities management (ALM) structure and instrument in Islamic banking. Since in Islamic banking depositors take partnership in benefits of the bank, so Islamic banking follows to maximizing benefits of beneficiaries and among them depositors. Therefore, there are dissimilarities between ALM approaches in Islamic banking and conventional banking. First, this dissimilarity comes from differences in the accounting system in Islamic banking in comparison to conventional banking. Secondly, usury illegalness and its related jurisprudence specifications indicate that time is not the solely the effective factor on increasing equity (deposited capital) return; but profit and loss sharing resulted from investment in the real economy sector is the essential base in monetary transactions. These two important factors are considerable factors in Islamic ALM.Design/methodology/approach: we consider influence specifications of these factors in two banking approaches for creating Economic Value Added (EVA).Findings: Comparison of financial indices for the two types of banking leads us that Islamic banking is more efficient than conventional banking.